Creation of the environment of wetlands with the use of drainage - Rzyczniak, Mirosław; Rzyczniak, Anna (My University, 2015)
In the article there was represented the example of a project concerning dehydration of agricultural lands located in Rzozów in the area of Skawina commune, administrative district of Kraków in Małopolska, around 16 km long distant to the west – south from the city centre of Kraków. The analised land is being under the disadvantageous hydro and air conditions, what results in the significant decrease of grounds quality and plants crops as the consequence. In order to improve the quality of grounds and dehydrate the excess of water, there was designed a dehydration system consisted of open drainage ditches and underground drainage network. The aim of those operations is to improve the ground structure quality and it’s access to air, thus to increase the plants crops from the presented area. There were lead numerous calculations such as hydrological calculations, hydraulic calculations in order to define type and height of drainage ditches consolidation and the height of collector mouths over the ditch bottom, calculations of drains spacing and the excavation capacity. As the final effect, it was assumed to excavate two drainage ditches, one on the northern side and one on the southern side of the area. The network of drains and collector connected to the ditches is to drain off the spare water from the considered land.
AGH Drilling, Oil, Gas
Keywords: ground dehydration; drainage; natural environment creation